PATHOPHYSIOLOGICAL MECHANISMS OF NITROGEN METABOLISM DYSREGULATION UNDER THE INFLUENCE OF IONIZING RADIATION - Dimov, А.О.; Stepanov, G.F. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the pathophysiological mechanisms of dysregulation of nitrogen metabolism in animals after exposure to different doses of ionizing radiation. Male Wistar rats were exposed to ionizing radiation. Alanine- and aspartate aminotransferase activities were determined in the animals’ liver, blood, skeletal and cardiac muscles. The total nitrogen and its components content was determined in the urine and blood of rats. Data obrained demonstrated that ionizing radiation induces a pronounced, dose-dependent suppression of alanine- and aspartate aminotransferase activities in mitochondrial and cytoplasmic fractions of liver and cardiac muscle tissues, with the most severe impairments observed at 5.82 Gy, indicating significant depletion of cellular functional capacity and energy failure. In skeletal muscle, the decrease was mainly limited to mitochondrial fractions, while cytoplasmic enzyme activity remained relatively stable, suggesting higher tissue resistance to radiation injury. Blood analysis revealed a significant increase in transaminase activity, indicating systemic cytolysis, which may serve as a biomarker of radiation injury severity. In addition, radiation exposure led to a marked reduction in daily urine output, along with a significant increase in urinary nitrogen excretion and a dramatic rise in protein catabolism. These findings highlight the complex metabolic and functional impairments in vital organs and systems caused by ionizing radiation. The identified biochemical alterations may be utilized as informative biomarkers for early diagnosis, severity assessment, and monitoring of radiation injury, as well as for evaluating the effectiveness of radioprotective interventions.
Keywords: total body gamma irradiation; ionizing radiation; muscle tissue; liver; alanine aminotransferase; aspartate aminotransferase; total urinary nitrogen; pathophysiological mechanisms